Liquid junction potentials at mixed electrolyte salt bridges - Finkelstein, Noel Phillip (Rhodes University, Faculty of Science, Department of Chemistry, 1957)
The potentiometric method is one of the most exact techniques of electrochemistry. Its use is widespread in both routine measurements, such as pH determination, and in applications which demand the highest accuracy. Perhaps its severest limitation is the error due to liquid junction potentials. Although this has been the subject of much study, and although various means of combating it have been proposed, it has defied all attempts at a satisfactory solution. Indeed, so serious is the position that it has become the accepted practice in the more accurate fields to abandon altogether the use of potentiometric techniques in favour of others, usually less convenient and otherwise less accurate, when the presence of liquid junctions cannot be avoided. Intro. p. 1.
Keywords: Hydrogen-ion concentration -- Measurement; Hydrogen-ion concentration; Electrochemistry